Specific Features Of Language Units Expressing National Value In The Works Of Uzbek Writers - B.R.Shamsematova (Genius Journals, 2022)
The following article gives brief information about the specific features of language units expressing national value in Uzbek writers’ works
Keywords: National values; literature; valuable; manner